Kaidah Al Hazf dalam Rasm UtsmÄnÄ« - Misnawati, Misnawati (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Rasm 'UtsmÄnÄ« is a model for writing the Koran which was agreed during the Khalifah "UtsmÄn bin 'AffÄn by copying the manuscripts that had been collected at the time of Khalifah Abu Bakr al ShiddÄ«q into several manuscripts. Then the manuscripts sent to various Islamic areas along with the qurrÄ` to be used as guidelines by the Muslims. Scholars have different views regarding the 'UtsmÄni rasm as something that must be followed or not. Scholars have three opinions. First, Rasm 'UtsmÄn is tauqifÄ« (based on guidance from the Prophet SAW) and cannot violate it and must be followed by Muslims. Second, Rasm 'UtsmÄn is ijtihad but still must be followed by Muslims and must not violate it. Third, Rasm 'UtsmÄn is just a given term which may be violated if it is agreed by a generation to use another model of rasm. There are several rules contained in this 'UtsmÄnÄ« rasm, one of them is the al hazf (letter removal) rule. The rules of al-hazf are broadly divided into three, such as: hazf isyÄrah, hazf ikhtishÄr, and hazf iqtishÄr. From these three models, it can be seen that some letters were discarded, namely alif, waw, yÄ`, lÄm, and nun. Each of these letters has its own provisions in its writing in the Qur'an and has secrets that can be known through in-depth study.ABSTRAKRasm â€˜UtsmÄnÄ« merupakan model penulisan al-Qur`an yang disepakati pada masa Khalifah â€œUtsmÄn bin â€˜AffÄn dengan menyalin mushaf yang telah dikumpulkan pada masa Khalifah Abu Bakar al ShiddÄ«q ke dalam beberapa mushÄf. Lalu dikirim ke berbagai wilayah Islam bersama dengan para qurrÄ` untuk dijadikan pedoman oleh kaum muslimin. Ulama berbeda pandangan dalam melihat rasm â€˜UtsmÄni sebagai sesuatu yang wajib diikuti atau tidak. Ada tiga pendapat ulama. Pertama, Rasm â€˜UtsmÄnÄ« bersifat tauqÄ«fÄ« (berdasarkanÂ  bimbingan dari Nabi SAW) dan tidak boleh menyalahinya serta wajib Â diikuti oleh kaum muslimin. Kedua, Rasm â€˜UtsmÄnÄ«Â  bersifat ijtihad namun tetap wajib diikuti oleh kaum muslimin serta tidak boleh menyalahinya. Ketiga, Rasm â€˜UtsmÄnÄ« hanyalah sebuah istilah yang diberikan yang boleh saja menyalahinya jika memang disepakati oleh suatu generasi untuk menggunakan model rasm yang lain. Ada beberapa kaidah yang terdapat dalam rasm â€˜UtsmÄnÄ« ini, salah satunya adalah kaidah al hazf (pembuangan huruf). Kaidah al hazf ini secara garis besar terbagi tiga yaitu: hazf isyÄrah, hazf ikhtishÄr, dan hazf iqtishÄr. Dari ketiga model ini terlihat ada beberapa huruf yang dibuang yaitu alif, waw, yÄ`, lÄm, dan nÅ«n. Masing- masing huruf tersebut memiliki ketentuan- ketentuan tersendiri dalam penulisannya dalam al-Qur`an dan mempunyai rahasia yang dapat diketahui melalui kajian yang mendalam. Â Â